Medication Compliance Analysis in Pulmonary Tuberculosis Patients at Bekasi Jaya Health Center Indonesia - Zulfa Rindy Al Fitry; Erlina Puspitaloka Mahadewi; Ade Heryana; Ira Marti Ayu (CV. Inara, 2022)
Tuberculosis is an infectious disease caused by the bacterium mycobacterium tuberculosis. Compliance with taking medication is a key factor in the success of tuberculosis treatment. Medication non-adherence can increase the risk of treatment failure and relapse, and is considered one of the most important causes of drug resistance. Compliance with taking medication is the patient's actions related to patient compliance in the process of taking routine drugs and consuming routine drugs during the intensive and advanced stages of treatment as determined. Based on observations by distributing questionnaires at the Bekasi Jaya Health Center Indonesia in January to October 2021 for patient compliance, the results obtained were 62% obedient and about 38% of patients were not compliant in taking medication. The purpose of this study was to determine the analysis of drug adherence in pulmonary tuberculosis patients at the Bekasi Jaya Health Center. This study uses a descriptive quantitative research methodology with a cross sectional research design. The sample in this study is the total population of 37 people, and conducted by filling out a questionnaire by the patient. Data analysis was performed with Univariate and Bivariate analysis. The results of the univariate analysis in this study showed that the highest proportion of respondents who had higher education was 65%, respondents who did not work were 65%, good knowledge was 65%, the availability of health facilities and facilities of respondents who said complete was 65%, access to health services was 68% of respondents stated that it was not difficult, 86.5% of their family support was good, 68% of health workers' support was good. This study also found the results of bivariate analysis that there was a relationship between educational status (p = 0.039; PR = 2.46; 95% CI = 1.089-5.563), medication adherence (p = 0.039; QR = 2.46; 95% CI = 1.09-5.56), availability of health facilities and facilities (p = 0.039 ; QR = 2.46 ; 95% CI = 1.09 – 5.56), access to health services (p = 0.006 ; QR = 3.32; 95% CI = 1.46-7.85), family support (p = 0.039; QR = 2.46; 95% CI = 1.09 – 5.56), and support from health workers (p = 0.027 ; QR = 2.78 ; 95% CI = 1.24 – 6.21) with medication adherence. In addition, the study also found that there was no relationship between work status and medication adherence (p = 1,000; PR = 0.97; 95% CI = 0.42–2.3). The proportion of family support for tuberculosis patients was dominated, because of this, it is necessary to make efforts to increase public awareness of the working area of the health centerabout the importance of medication adherence in tuberculosis patients. The more active health workers and other related sectors, can increase the rate of adherence to taking medication for pulmonary tuberculosis patients in the work environment at Bekasi Jaya Health Center, Indonesia.